2016
DOI: 10.1128/jcm.01255-16
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: The First Fully Automated Molecular Diagnostic Panel for Meningitis and Encephalitis: How Well Does It Perform, and When Should It Be Used?

Abstract: Meningitis and encephalitis are potential infectious disease emergencies. The laboratory evaluation of suspected meningitis/encephalitis (ME) is complex, in part because the differential diagnosis is broad and the associated clinical signs and symptoms are not organism specific. Clinicians typically prioritize laboratory workup based on host factors, the duration of symptoms, and potential environmental exposures; but cerebrospinal fluid (CSF) indices in combination with multiple microbiologic tests are genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…This might raise the question if using in-house PCR assays for HSV, enterovirus and HHV-6 instead of using the mPCR, may be more cost effective in some institutions. Some authors even implied that the sensitivity of a singleplex assay to detect viral agents is greater than that of a mPCR [15,17,44]. However, this approach involves the risk of missing a viral pathogen and requires a certain level of medical experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might raise the question if using in-house PCR assays for HSV, enterovirus and HHV-6 instead of using the mPCR, may be more cost effective in some institutions. Some authors even implied that the sensitivity of a singleplex assay to detect viral agents is greater than that of a mPCR [15,17,44]. However, this approach involves the risk of missing a viral pathogen and requires a certain level of medical experience.…”
Section: Discussionmentioning
confidence: 99%
“…mPCR) on empiric treatment. Quick verification or exclusion of the presence of organisms may enable clinicians to early optimize antimicrobial therapy and hence possibly reduce therapy-associated complications and healthcare costs [15][16][17][18]. In a previous study conducted at our institution we retrospectively analyzed all patients receiving mPCR testing over the period of one year [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of fever, stiff neck, and altered mental status allowed clinicians to exclude meningitis with 99 to 100% confidence. 7 Overall, the classical triad of meningitis with fever, neck stiffness, and altered mental state in our study was 46.1%. A study conducted in patients of 16 years and older found that the triad of fever, neck stiffness, and altered mental state was observed in only 44 to 46%.…”
Section: Discussionmentioning
confidence: 44%
“…Fifty CSF samples stored in a À 70°C freezer (40 suspected meningitis and 10 suspected encephalitis) were tested using meningitis/encephalitis (ME) panel for FilmArray multiplex polymerized chain reaction (PCR) system. It targets 14 potential pathogens 7,8 CSF parameters including differential cell count, protein concentration, and glucose ratio in CSF and blood were used to aid the etiological diagnosis. 10 Further, depending on clinical suspicion, magnetic resonance imaging (MRI) or computed tomography or ultrasound scan of brain of the infants was performed, to detect space-occupying lesions and to assess structural malformations.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, in their clinical trial, Leber et al also reported false-positive results for S. pneumoniae, S. agalactiae, and E. coli and a false-negative result for S. agalactiae. Others who have reviewed these results have remarked that institutions using FilmArray ME may wish to consider implementing clinician counseling by clinical laboratories and/or ASP to ensure that positive and negative results are interpreted appropriately [29].…”
Section: Rdts In Meningitis and Encephalitismentioning
confidence: 99%